Creating the Right Conditions for Language Learning: The Classroom as a Learning Environment (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The success of language acquisition is significantly influenced by the learning environment, particularly the physical and social dimensions of the classroom. This article explores the key factors that contribute to an effective language learning environment, focusing on strategies that foster engagement, interaction, and a sense of community. It examines the impact of physical layout, pedagogical approaches, technology integration, and teacher-student relationships on language acquisition. Recommendations are offered for educators to create classrooms that promote active learning, reduce anxiety, and maximize language acquisition opportunities.